Exon 11 homozygous mutations and intron 10/exon 11 junction deletions in the KIT gene are associated with poor prognosis of patients with gastrointestinal stromal tumors. (22nd July 2020) - Shen, Yan‐Ying; Ma, Xin‐Li; Wang, Ming; Zhuang, Chun; Ni, Bo; Tu, Lin; Liu, Qiang; Zhao, Wen‐Yi; Cao, Hui
Abstract: Background: Gastrointestinal stromal tumors (GISTs) with different types of mutations exhibit different clinical characteristics and prognosis. This study aimed to evaluate the prognostic value of mutations in KIT and PDGFRA in a large‐scale cohort of GIST patients with current therapy including surgery and imatinib. Methods: A total of 1163 patients diagnosed with GISTs between January 2006 and December 2018 were enrolled in this study. Mutation analysis was performed for exons 9, 11, 13, and 17 of KIT and exons 12 and 18 of PDGFRA . Mutations were grouped into 12 categories according to the gene, exon, and involved codons; they were analyzed considering the clinical characteristics, disease‐free survival (DFS), and overall survival (OS) of patients with GISTs. Results: In low‐risk GISTs, we identified two predictors of worse DFS: tumor origin in the rectum and KIT exon 11 deletion involving two or more codons. In high‐risk GISTs treated with R 0 resection and imatinib, patients with KIT exon 11 homozygous mutations and KIT intron 10/exon 11 junction deletions demonstrated the highest recurrence rate, indicating that these mutations can be independent prognostic factors of DFS. The presence of KIT exon 11 homozygous mutations also independently influenced OS. Conclusion: Low‐incidence mutations such as KIT exon 11 homozygous mutations or intron 10/exon 11 junction deletions in GISTs should be carefully evaluated to explore novel treatment strategies, as tumors with these mutations have a high recurrence rate and a very poor prognosis after surgery followed by imatinib adjuvant treatment. Abstract : Low‐incidence mutations such as KIT exon 11 homozygous mutations or intron 10/exon 11 junction deletions in GISTs should be carefully evaluated to explore novel treatment strategies, as tumors with these mutations have a high recurrence rate and a very poor prognosis after surgery followed by imatinib adjuvant treatment.